Bekomme Prokrastination in den Griff und beherrsche Deinen Tag (Assemble You, 2022)
Welcome to our Assemble You Learning Podcast In a survey of more than 2,000 people, 88% of respondents admitted to procrastinating for at least an hour a day, and almost 60% admitted to procrastinating for more than two hours a day. If you want to make the most of your time to be more productive and successful, listen to the 5 tips in this 10-minute podcast. Learning Objectives Learn 5 Anti-Procrastination Tips to Increase Your Productivity Learn to take control of your time and get more out of your day.